Etude des Propriétés Optoélectroniques et Magnétiques des Composés ZnX/CdX Dopés par des Métaux de Transition - BENSTAALI WISSAM (My University, 2015)
Electronic, magnetic and optical properties of ZnSe and CdS both of them doped by different transition metals have been studied in this thesis, using the method of linearized augmented plane wave (FP- LAPW) based on DFT with the LSDA approximation. Using the WIEN2k code , for the electronic properties , in most cases, the results obtained showed an emergence of new states around the Fermi level which are mainly due to the d levels of the transition metals and appearance of an asymmetry between the high spin and low spin . This allows the use of these compounds in spintronics. For the magnetic properties, it has been found that after doping, magnetic materials were obtained except for materials doped by Cu which doesn’t cause any change of magnetism due to the saturation of the d level. Finally, for optical properties, we found that after doping, we have the appearance of peaks in lower frequencies and an offset of optical curves is obtained towards the low frequencies or towards the high frequencies.
Keywords: DFT, Spintronic, LSDA, Optical Properties and Fermi Level